Exploring turbulence from the Sun to the local interstellar medium: Current challenges and perspectives for future space missions - Fraternale, Federico; Zhao, Lingling; Pogorelov, Nikolai V.; Sorriso-Valvo, Luca; Redfield, Seth; Zhang, Ming; Ghanbari, Keyvan; Florinski, Vladimir; Chen, Thomas Y. (Frontiers in Astronomy and Space Sciences, 2022)
Turbulence is ubiquitous in space plasmas. It is one of the most important subjects in heliospheric physics, as it plays a fundamental role in the solar wind - local interstellar medium interaction and in controlling energetic particle transport and acceleration processes. Understanding the properties of turbulence in various regions of the heliosphere with vastly different conditions can lead to answers to many unsolved questions opened up by observations of the magnetic field, plasma, pickup ions, energetic particles, radio and UV emissions, and so on. Several space missions have helped us gain preliminary knowledge on turbulence in the outer heliosphere and the very local interstellar medium. Among the past few missions, the Voyagers have paved the way for such investigations. This paper summarizes the open challenges and voices our support for the development of future missions dedicated to the study of turbulence throughout the heliosphere and beyond.